Case report: Successful anesthesia management of noncardiac surgery in a patient with single atrium - Cao, Hong; Jiang, Mengmeng; Zhuang, Zhao; Wang, Shoushi; Cao, Qianqian (Frontiers in Pharmacology, 2024)
Background: Single atrium is very rare congenital cardiac anomaly in adults. The prognosis of patients with single atrium is very poor, with 50% of patients dying owing to cardiopulmonary complications in childhood. Herein, we focused on anesthesia management for noncardiac surgery in patients with single atrium.Case presentation: A 58-year-old male with a history of bilateral varicocele underwent laparotomy for high-position ligation of the spermatic vein. The patient also had a history of single atrium, atrial fibrillation, chronic heart failure, pulmonary hypertension (PH), and complete right bundle branch block (CRBBB). Given the significant complications associated with general anesthesia in patients with PH, we preferred to use low-dose epidural anesthesia for this patient. Transthoracic echocardiography was used to assess cardiac function before and during surgery and guide perioperative fluid therapy. To limit the stress response, we used a regional nerve block for reducing postoperative pain. Furthermore, we used norepinephrine to appropriately increase the systemic vascular resistance in response to the reduction of systemic vascular resistance caused by epidural anesthesia.Conclusions: Low-dose epidural anesthesia can be safely used in patients with single atrium and PH.The use of perioperative transthoracic echocardiography is helpful in guiding fluid therapy and effectively assessing the cardiac structure and function of patients. Prophylactic administration of norepinephrine before epidural injection may make it easier to maintain the patient's BP.